1999
DOI: 10.1002/(sici)1099-0682(199909)1999:9<1563::aid-ejic1563>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Stanna-closo-dodecaborate: A Nucleophile in Transition Metal Chemistry

Abstract: Reactions of the stannaborate salt [NBu4]2[SnB11H11] (1) with the organometallic electrophiles [CpFe(CO)2Br], [(C7H7)Mo(CO)2I], and [CpNi(PPh3)Cl] resulted in substitution of the halide to give the stannaborate coordination products [NBu4][CpFe(CO)2(SnB11H11)] (2), [NBu4][(C7H7)Mo(CO)2(SnB11H11)] (3), and [NBu4][CpNi(PPh3)(SnB11H11)] (4) in high yields. Single crystals of the air‐ and moisture‐stable products have been characterized by X‐ray crystal structure analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…NMR spectra were obtained using a Bruker DRX-250 NMR spectrometer equipped with a 5 mm ATM probe head and operating at 250. 13…”
Section: Quantum-chemical Calculationsmentioning
confidence: 99%
“…NMR spectra were obtained using a Bruker DRX-250 NMR spectrometer equipped with a 5 mm ATM probe head and operating at 250. 13…”
Section: Quantum-chemical Calculationsmentioning
confidence: 99%
“…[6,7] We found that stanna-closo-dodecaborate [SnB 11 H 11 ] 2À can coordinate to transition metal centers. [8] The synthesis of the ligand is straightforward and results in the isolation of gram amounts of the cluster with a variety of counter cations. The transition metal derivatives are, like the ligand, stable towards moisture and air.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this geometry, a relatively narrow range of MÀSn bond lengths was also measured for each of the three compounds (2.534(1)-2.548(1), 2.612(1)-2.614(1), 2.616(1)-2.619(1) , respectively). The Ni À Sn bond lengths measured for 1 a are significantly longer than those measured for the same stannaborate ligand in [CpNi(PPh 3 )-(SnB 11 H 11 )] À (2.412(1) ) and [Ni(SnB 11 H 11 ) 4 ] 6À (2.471(1) and 2.476(1) ; see below), [10] but are well within the sum of the [11] Given that each of these lower-symmetry systems features a formal Ni II center (in contrast to Ni IV in 1 a), the increased bond lengths for 1 a are clearly a manifestation of the high degree of steric crowding inherent in accommodating six bulky donor groups at the Ni IV center (the ionic radii for Ni IV and Ni II are 0.48 and 0.69 , respectively). [11] The NMR spectra of 1 a-c in dichloromethane or THF were measured with the aim of establishing the composition of these species in solution.…”
mentioning
confidence: 83%